Point-of-Care Testing (POCT) for Blood Gas and Electrolyte Analysis in Out-of-Hospital Cardiac Arrests’ Management; a Cross-sectional Study - Tienpratarn, Welawat; Yuksen, Chaiyaporn; Chukaew, Lunlita; Jenpanitpong, Chetsadakon; Triganjananun, Chavin; Seesuklom , Suteenun (Archives of Academic Emergency Medicine, 2025)
Introduction: Hypokalemia, hyperkalemia, and acidosis are among the reversible causes of out-of-hospital cardiac arrest (OHCA) that can be promptly identified using point-of-care testing (POCT) for blood gas and electrolyte analysis. This study aimed to evaluate the efficacy of POCT in the prehospital setting for OHCA management. Methods: In this cross-sectional study the management and outcomes of OHCA patients were compared before and after implementing the POCT for blood gas and electrolyte analysis by EMS in the prehospital setting of Ramathibodi Hospital, Thailand. Results: 217 OHCA patients with a mean age of 61 ± 17.07 (range: 58.72-63.28) years were studied (64.06 % male). 148 (68.2%) patients received POCT in the prehospital setting. Patients in the POCT group received higher administration of sodium bicarbonate (p < 0.001) and calcium gluconate (p < 0.001) compared to those without POCT. Sustained ROSC was achieved in 25% of the POCT group, compared to 11.59% in the no POCT group (p = 0.030). POCT blood gas analysis was identified as an independent predictor of sustained ROSC based on multivariable analysis (adjusted Odds: 4.60, 95% CI: 1.35-15.69; p = 0.015). Conclusions: It seems that POCT for blood gas and electrolyte analysis in the prehospital setting could improve sustained ROSC in OHCA patients by enabling rapid and targeted management of cardiac arrest’s reversible causes.